Stress, glucocorticoid signaling pathway, and metabolic disorders - de Guia, Roldan M (Diabetes & metabolic syndrome, 2020)
BACKGROUND AND AIMS: Glucocorticoids and the GR serve as an essential molecular mediator of stress and different physiologic processes. This review summarizes main findings from studies on the role of the GC/GR signaling in the modulation of genes for nutrient processing by the different organs involved in metabolic diseases. METHODS: Descriptive review of relevant papers known to the author was conducted. RESULTS: Several high-throughput screenings in the past 15 years have identified potential GR DNA-binding regions in different cell types with genes that are annotated to be important for the control of metabolism. Transcriptional regulation of these GC-responsive genes provides links between the hypothalamic-pituitary-adrenal axis (HPA) and systemic energy homeostasis in both physiological and pathophysiological states. Future studies must reconsider the use of agonist, the utilization of animal models of stress and metabolic disorders, and validation in humans. CONCLUSION: This review recapitulates the significant role of the GC/GR signaling in molecular metabolic control and metabolic disorders. Potential future research focus and optimizations have also been identified.
Keywords: Humans; Metabolic Diseases; Metabolic disorders; Glucocorticoids; signální transdukce; glukokortikoidy; metabolické nemoci; Stress, Physiological; Metabolism; fyziologický stres; lidé; Glucocorticoid receptor; Signal Transduction